Improving Innovative Work Behavior in the Hospitality Sector: The Mediation Role of Knowledge Sharing between Transformational Leadership and Psychological Capital - Ramadhan, Sukmadianto Tri; Bagis, Fatmah; Tubastuvi, Naelati; Arofah, Rifka Utami (Asian Journal of Management Analytics, 2025)
This study aims to empirically test a research model that investigates the impact of transformational leadership and psychological capital on innovative work behaviors and examine the role of knowledge sharing as a mediator. The population in this study is 255 and the sample used is 162 hospitality sector employees in Banyumas. The questionnaire was given online using a google form, and sampling was carried out using an accidental sampling approach. Partial Least Squares (PLS) are used to analyze the collected data. The results of this study show that transformational leadership and psychological capital have a positive and significant effect on innovative work behaviors. Knowledge sharing successfully mediates positively and significantly between transformational leadership and psychological capital towards innovative work behaviors.